Statistician, heal thyself: fighting statophobia at the source - Aksentijevic, Aleksandar (Frontiers in Psychology, 2015)
Notwithstanding the popularity of psychology courses throughout the world, educators face a constant and difficult problem of overcoming the fear of and dislike for statistics which represents one of the pillars of modern psychological science. Although the issue is complex and multifaceted, here I argue that “statophobia” might represent a rational and justified response to the sense of unease felt in contact with abstract statistical concepts which are often vague, circular or ill-defined. I illustrate the problem by briefly discussing two myths about the nature of probability and statistics, namely that probability and statistics generate knowledge and that the fault for not understanding probability lies solely with the subjective cognition which is incapable of comprehending deeper mathematical truth. I argue that the confident presentation of statistical methods hides numerous conceptual blind spots that students might be aware of and that need to be addressed before other causes of statistics anxiety can be tackled successfully.